Equilibration Dependence of Fucoxanthin S1 and ICT Signatures on Polarity, Proticity, and Temperature by Multipulse Femtosecond Absorption Spectroscopy - West, Robert G; Fuciman, Marcel; Staleva-Musto, Hristina; Šebelík, Václav; Bína, David; Durchan, Milan; Kuznetsova, Valentyna; Polívka, Tomáš (The journal of physical chemistry. B, 2018)
To demonstrate the value of the multipulse method in revealing the nature of coupling between excited states and explore the environmental dependencies of lowest excited singlet state (S1) and intramolecular charge transfer (ICT) state equilibration, we performed ultrafast transient absorption pump-dump-probe and pump-repump-probe spectroscopies on fucoxanthin in various solvent conditions. The effects of polarity, proticity, and temperature were tested in solvents methanol at 293 and 190 K, acetonitrile, and isopropanol. We show that manipulation of the kinetic traces can produce one trace reflecting the equilibration kinetics of the states, which reveals that lower polarity, proticity, and temperature delay S1/ICT equilibration. On the basis of a two-state model representing the S1 and ICT states on the same S1/ICT potential energy surface, we were able to show that the kinetics are strictly dependent on the initial relative populations of the states as well as the decay of the ICT state to the ground state. Informed by global analysis, a systematic method for target analysis based on this model allowed us to quantify the population transfer rates throughout the life of the S1/ICT state as well as separate the S1 and ICT spectral signatures. The results are consistent with the concept that the S1 and ICT states are part of one potential energy surface.